121k views
3 votes
Here is our problem

Here is a system of linear equations
Equation 1: y= x-2
Equation 2: y =-2x+13
The following system of equations was obtained by adding a multiple of Equation 2 to Equation 1.
Equation 3: y= x-2
Equation 4: 4y= 5x +37

1 Answer

6 votes

Answer:

x = 5 and y = 3 solution is (5, 3)

Explanation:

y = x - 2 multiply each term by 2

y = -2x + 13 Do not change

2y = 2x - 4

y = -2x + 13

3y = 9

y = 9/3

y = 3

y = x - 2 Substitute y = 3 and solve for x

3 = x - 2

5 = x

User Jspizziri
by
4.7k points